Alterations in serum growth hormone (GH)/GH dependent ternary complex components (IGF-I, IGFBP-3, ALS, IGF-I/IGFBP-3 molar ratio) and the influence of these alterations on growth pattern in female rhythmic gymnasts - Adiyaman, P.; Öcal, G.; Berberoglu, M.; Evliyaoglu, O.; Aycan, Z.; Cetinkaya. E.; Bulca, Y.; Ersöz, G.; Akar, N. (Journal of Pediatric Endocrinology and Metabolism, 2011)
Normal growth in children is regulated to a great extent through the actions of the GH/IGF-I axis, a system consisting of GH and its mediators (ternary complex) that modulate growth in many tissues. The ternary complex (IGF-I/IGFBP-3/ALS) provides an acute regulatory mechanism in which IGF-I may be mobilized from the circulating reservoir of 150 kDa complexes to the tissues. Acute exercise is known to be a stimulus for GH secretion. The beneficial effects of scheduled exercise on body composition are also well established. However, the impact of strenuous exercise on the pubertal development of child athletes is still not well understood. The first goal of this study was to assess the acute effects of high intensity exercise training on GH-dependent ternary complex components in female rhythmic gymnasts compared to age-matched healthy female controls with normal physical activity. The second goal was to explore the influence of these exerciseinduced changes on skeletal and pubertal growth in the same group prospectively over a period of 4 years. Subjects and Methods: Seventeen female rhythmic gymnasts, aged 11.4 ± 0.9 years, who had 10 h per week intense exercise for at least 4 months volunteered to participate in this study. Anthro- pometric measurement of height (Height SDS for chronological age [HtSDScA], parentally adjusted height, predicted adult height), bone age and weight (BMI) were made using standard techniques in gymnasts and controls (aged 12.5 ± 3.0 years, . = 12). Gymnasts were followed up to 4 years to observe growth velocity and pubertal progression. In order to determine the acute impact of exercise on levels of GH and GH-dependent ternary complex component (IGF-I, IGFBP-3, ALS, IGF-I/IGFBP-3 molar ratio), blood samples were obtained from gymnasts after a routine 2-h high-intensity trainingprogram and then after a 2-day rest period. These results were compared with age-matched controls with no scheduled sports activity. Results: Despite the significant increment in serum GH and GH-dependent components immediately following the exercise, serum GH/IGF-I levels showed a significant decrement (p <0.01) after a 2-day rest in gymnasts, to a nadir as low as those of the control subjects' baseline levels (p <0.01). There was no difference in anthropometric characteristics of gymnasts and controls except BMI; gymnasts were leaner than controls. During a 4-year follow up, there were no differences between the gymnasts and controls in regard to skeletal growth and reaching their predicted height. However, in gymnasts there was a delay in pubertal tempo but not in growth. Conclusion: Intense exercise induces an acute rise in GH levels, but this acute elevation rapidly normalizes after a 2-day rest in female rhythmic gymnasts. These fluctuations in serum GH and GH-dependent ternary complex components had no reflection on the skeletal growth patterns in gymnasts over the 4-year follow up but there was a delay in their pubertal progression.